Electrochemical Pretreatment of Solid‐Electrolyte Interphase Formation for Enhanced Li4Ti5O12 Anode Performance in a Molten Li−Ca Binary Salt Hydrate Electrolyte. Issue 11 (29th April 2022) - Kondou, Shinji; Watanabe, Yoshifumi; Dokko, Kaoru; Watanabe, Masayoshi; Ueno, Kazuhide
Abstract: Water‐in‐salt electrolytes have been widely explored because of their expanded electrochemical stability (>3.0 V). However, the instability of solid‐electrolyte interphase (SEI) in aqueous electrolytes leads to their reductive decomposition on the negative electrodes of low‐potential anode materials. Here, we demonstrate significant improvement in the cycle performance of a Li4 Ti5 O12 electrode using a Li−Ca binary salt hydrate (LCH) electrolyte in combination with an optimized electrochemical pretreatment process. Compared with a hydrate‐melt electrolyte, the LCH electrolyte provided less water‐soluble Ca‐based SEI components, and careful pretreatment process enabled the formation of a thicker SEI layer on the Li4 Ti5 O12 electrode. Protected with the hardly soluble, thick SEI layer, the Li4 Ti5 O12 electrode effectively mitigated unfavorable side reactions and achieved 95.5 % capacity retention over 50 cycles. These results offer insight into a promising route for stable SEI layer formation for the practical use of low‐potential anode materials in aqueous rechargeable lithium‐ion batteries. Abstract : Li−Ca binary salt hydrate : Significant improvement in the cycle performance of a Li4 Ti5 O12 electrode was achieved using a Li−Ca binary salt hydrate (LCH) electrolyte in combination with an optimized electrochemical pretreatment process. The LCH electrolyte provided less water‐soluble Ca‐based SEI components, and careful pretreatment process enabled the formation of a thicker SEI layer on the Li4 Ti5 O12 electrode, leading to 95.5 % capacity retention over 50 cycles.